Comparison of Sublingual Misoprostol and Per Vaginal Dinoprostone for Induction of Labour - Abid, Purnoor; Hussain, Abid; Gul, Hina; Ishtiaq, Yamina; Yaqoob, Nida; Yaqoob, Anum (Indus Journal of Bioscience Research, 2025)
Introduction: Misoprostol and dinoprostone are two widely used induction agents. Our study was designed to compare both these drugs in terms of induction to labour time, ceserean section rate and meconium staining. Objective: To compare the outcome of sublingual misoprostol and per-vaginal dinoprostone for induction of labour. Methods: A total of 110 patients were enrolled using blocked randomization sampling, with 55 patients in each group. The primary outcome was the mode of delivery. The need for an emergency cesarean section was recorded in cases of reduced labor pains, failed induction, pathological cardiotocography, or thick meconium-stained liquor. Additional outcome variables were determined for all enrolled subjects which were the success of induction (induction was considered successful if delivery occurred within 12 hours of induction), induction-to-delivery interval (the time from induction to fetal delivery was recorded in minutes), meconium passage and the total number of doses administered from the first dose until delivery. Results: Both groups exhibited comparable baseline characteristics, including age, BMI, gestational age, and parity. Dinoprostone was shown to be better than misoprostol in all study outcomes. Conclusions: Our study suggests that dinoprostone was associated with a significantly shorter induction-to-delivery interval and a higher proportion of deliveries within 12 hours compared to misoprostol. The increased incidence of meconium-stained amniotic fluid in the misoprostol group highlights a potential risk factor that needs further investigation.